Self : driving positive psychology and wellbeing - Guay, Frédéric; Marsh, Herbert W.; McInerney, Dennis M.; Craven, Rhonda G. (International advances in self research., 2017)
Research on the Self relates to various phenomena including self-esteem, self-concept, self-verification, self-awareness, identity, self-efficacy, passion, self-determination, goals etc. that are predictive of optimal functioning and well-being. Such a research endeavor is consistent with the positive psychology movement focusing on the scientific study of what makes people psychologically healthy, happy, and satisfied in their lives, as well as on their strengths and virtues. The positive psychology movement cultivates a sensible approach to optimal human functioning and well-being in various life contexts. Chapters in this volume will illustrate some of the best of the research on the interplay between the self and positive psychology, to show the potential of this research for transforming our societies.SELF - Driving Positive Psychology and Well-being thus provides a unique insight into self and its fundamental role for well-being. This volume is intended to develop both theoretical and methodological ideas and to present empirical evidence of various phenomenon important for well -being. The scope of the volume is thus very broad, and provides a framework for the development of the chapter as authors see most appropriate.